Let's separate the hexagon into 5 shapes; 2 triangles on each side, and a rectangle in the middle. Now let's find the area of each of the smaller shapes.
Top left triangle:The equation to find the area of a triangle is
(base = b, height = h, a = area)
a = b · h ·
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
Now let's add in our values and solve.
a = 2 · 4 ·
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
a = 8 ·
![\frac{1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20)
a =
4Now since there are 4 of these triangles, and they're all the same size,
4 · 4 =
16All of the triangles put together =
16cm²The middle rectangle:The equation to find the area of a rectangle is simple:
(w = width, l = length, a = area)
a = w · l
Now let's put in our values and solve.
a = 4 · 8
a =
32The rectangle is
32cm²Now let's add the areas together.
32 + 16 =
48The answer is <span>
48cm²Hope this helped! If you have anymore questions or don't understand, please comment or DM me. :)
</span>
Pedro did 1,626 hits and ricky did 1,056. Can you please help me with my question?
Answer: 37.5%
Step-by-step explanation: 1/8 is 12.5% and if you multiply 12.5 by 3 you get 37.5
Part A: Yes, the data represent a function. The definition of a function is a relation in which no value of x will have two different values of y.
(Every time you plug in 3 as x, you will always get 4 as y; it's ok if you plug in 3 and 5 as x and get the same y, you just can't get two different y's for one x; sorry, it is pretty confusing). None of the numbers in the table repeat, so we can safely say that the relation is a function.
Part B: All we have to do is plug in 11 for x in the function given to find the answer:
![f(x)=5x-21\\f(x)=5(11)-21\\f(x)=55-21\\f(x)=34](https://tex.z-dn.net/?f=f%28x%29%3D5x-21%5C%5Cf%28x%29%3D5%2811%29-21%5C%5Cf%28x%29%3D55-21%5C%5Cf%28x%29%3D34)
In the table, y = 8 when x = 11, but in the function given, y = 34 when x = 11, so the function given is greater.
Part C: To find the answer to C, just plug in 99 for f(x), as it tells you to do:
Answer:
![a => b \equiv ( \neg a \ \lor \ b )](https://tex.z-dn.net/?f=a%20%3D%3E%20b%20%20%20%5Cequiv%20%20%20%28%20%5Cneg%20a%20%20%20%5C%20%5Clor%20%20%20%5C%20b%20%29)
Step-by-step explanation:
You can understand the statement from many perspectives, but in terms of proposition logic it is best to understand it as "negation of a" or " b" in mathematical terms is written like this
![a => b \equiv ( \neg a \ \lor \ b )](https://tex.z-dn.net/?f=a%20%3D%3E%20b%20%20%20%5Cequiv%20%20%20%28%20%5Cneg%20a%20%20%20%5C%20%5Clor%20%20%20%5C%20b%20%29)
You can show that they are logically equivalent because they have the same truth table.